Monitoring microplastics in the Seine River in the Greater Paris area - Stratmann, Cleo N.; Dris, Rachid; Gasperi, Johnny; Buschman, Frans A.; Markus, Adriaan A.; Guerin, Sabrina; Vethaak, A. Dick; Tassin, Bruno (Frontiers in Earth Science, 2024)
This data paper presents microplastic (MP) concentration and composition data from four campaigns in a one-year period in the Seine River within the Greater Paris area. Detailed data on MP occurrence, physical water parameters, hydrological conditions, and potential sewer point sources are presented. Initial analysis of the data set shows that MP concentrations were significant (median: 600 particles m−3 and 100 mg m−3) and MP fluxes showed variations across sampling sites and campaigns. Three polymer types (polypropylene - PP, polyethylene - PE, polystyrene - PS) account for 96% of the total number of MP. This dataset provides valuable insights for understanding river MP pollution under anthropogenic pressure.